(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
A fiber optics is a transparent, flexible fabric made of plastic or glass with a diameter slightly bigger than human hair. It’s mostly used to transmit light from one fiber end to the other. This kind of transmission is often used in fiber optic communication, where an optic fiber link delivers data over a longer distance and with a higher bandwidth than an electrical line. The optical fiber communication system and network is now undergoing a significant transformation from a static, scalable, energy-efficient, and flexible design to a dynamic, scalable, energy-efficient, and adaptable approach. We look at the evolution of optical network technologies and methods in the fifth century in this article. The fibre optics biosensor is extremely important in the production of biosensors since it helps to quickly miniaturise and integrate those targets. Fiber optics has advanced dramatically since the fourth generation, with data rates reaching 40-60 tbps, repeater spacing reaching 35000 km, and wavelengths reaching 1.5 micrometres.